Cybercrime: challenges and difficulties for the administration of justice in Peru - Alcalá Molina, Félix Andrés (2025)
Significant advances in computing, telecommunications, and the internet have driven social, economic, and political progress, leading to a paradigm shift: from common crime to cybercrime. Cybercriminal activity has expanded globally, giving rise to new forms of illicit conduct and criminal activity online. This phenomenon has spread worldwide, resulting in punishable actions in cyberspace, committed through social networks, digital media, online environments, and mobile or technological devices. Consequently, legislators have had to restructure and adopt regulatory tools to prevent such crimes. Cyberspace lacks borders and legal regulations, which gives cybercriminals an advantage due to high complexity, anonymity, lack of evidence, and procedural legislation regarding electronic evidence. Currently, the role of the Public Prosecutor faces numerous challenges in the justice system, making investigation, criminal prosecution, and the formulation of accusations more difficult. Likewise, judicial bodies play a fundamental role: the Preliminary Investigation Courts are key in controlling legality; Criminal Courts conduct oral trials; and the Superior Courts assess procedural flaws and decide whether to modify, revoke, or uphold first-instance rulings. Cybercrime represents a growing challenge due to various factors, such as the constant evolution of technology and the use of advanced tactics, including artificial intelligence and deepfakes. Cybercriminals possess great capacity to exploit digital transformation to launch cyberattacks against networks and information systems. This study aims to analyze the challenges and difficulties faced by the Peruvian justice system in addressing this type of crime.